Restless Legs Syndrome: A Comprehensive Review of Current Treatment Methods and the Disease's Impact on Quality of Life - Natalie Papachristoforou; Natalia Tekiela; Daria Michałka; Zuzanna Gałuszka; Monika Makar; Tomasz Bartuś; Emilia Bąk; Justyna Głowacka; Aleksandra Kocjan; Radosław Chmiel (Quality in Sport)
Introduction and Purpose of Research: Restless Leg Syndrome (RLS) or Willis-Ekbom disease, is a common neurological disorder significantly impacting one’s sleep and quality of life. It often coexists with various health issues, including diabetes and cardiovascular diseases.